Work Recognition and Labor Productivity: Evidence from French Data†. (5th September 2014) - Grolleau, Gilles; Mzoughi, Naoufel; Pekovic, Sanja
Abstract : We empirically investigate whether labor productivity is related to work recognition. Using survey data about a large sample of French firms ( N = 5309), we find that firms in which employees think their work is recognized are likely to report higher labor productivity, compared with firms where employees do not feel recognized. Our estimation results also suggest that labor productivity is strongly related to wages. Copyright © 2014 John Wiley & Sons, Ltd.